2017
DOI: 10.1097/scs.0000000000003371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Mandibular Asymmetry in an Adult Population

Abstract: Mandibular asymmetry was not independently associated with sex, age, or absence of posterior teeth. The only verified independent association was between mandibular asymmetry and sagittal jaw relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 20 publications
3
46
0
Order By: Relevance
“…The following inclusion criteria had to be fulfilled: (a) children with transversal maxillary deficiency diagnosed by clinical examination showing intermolar width less than 34 mm and smile showing the buccal corridor and deep palate; (b) patients with or without functional UPC; (c) age between 4 and 10 years; (d) unilateral posterior crossbite involving at least two posterior teeth; and (e) cone beam computed tomography (CBCT) scans presenting no distortion or movement artefacts, appropriate field of view (FOV) and in maximum intercuspation. The exclusion criteria were as follows: (a) Class III patients (ANB < 0°) due its reported higher occurrence of mandibular asymmetry, (b) condylar imaging features of degenerative disease, such as erosion, subchondral cyst, generalized sclerosis or osteophytes, as defined by Schiffman et al, as well as condylar abnormal size suggestive of condylar hyperplasia; (c) history of facial or dental trauma; (d) syndromes or congenital craniofacial anomalies, such as cleft lip palate; (e) previous orthodontic or facial surgical procedures; (f) early loss of primary teeth or loss of permanent teeth; and (g) anterior crossbite.…”
Section: Methodsmentioning
confidence: 99%
“…The following inclusion criteria had to be fulfilled: (a) children with transversal maxillary deficiency diagnosed by clinical examination showing intermolar width less than 34 mm and smile showing the buccal corridor and deep palate; (b) patients with or without functional UPC; (c) age between 4 and 10 years; (d) unilateral posterior crossbite involving at least two posterior teeth; and (e) cone beam computed tomography (CBCT) scans presenting no distortion or movement artefacts, appropriate field of view (FOV) and in maximum intercuspation. The exclusion criteria were as follows: (a) Class III patients (ANB < 0°) due its reported higher occurrence of mandibular asymmetry, (b) condylar imaging features of degenerative disease, such as erosion, subchondral cyst, generalized sclerosis or osteophytes, as defined by Schiffman et al, as well as condylar abnormal size suggestive of condylar hyperplasia; (c) history of facial or dental trauma; (d) syndromes or congenital craniofacial anomalies, such as cleft lip palate; (e) previous orthodontic or facial surgical procedures; (f) early loss of primary teeth or loss of permanent teeth; and (g) anterior crossbite.…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral symmetry seems pervasive in the human body. It is also present in the normal craniofacial complex [47,48] with the mandible showing a symmetry of 82.85 (95% confidence interval 80-84.2), in a sample of 952 Brazilian individuals [49]. Thus, one would therefore presume that this would be the case for contralateral teeth.…”
Section: Epithelial-mesenchymalmentioning
confidence: 99%
“…[8][9][10] However, there were some differences related to the other variables that were analyzed. Some authors found that facial asymmetry was equally distributed in skeletal Class I, II, and III, 8 while others demonstrated asymmetry was more frequently associated with Class III, 6,10,22 or less common in Class II. 2 The current findings showed that severe MA was more frequent in skeletal Class III individuals, but moderate MA was more frequent in Class II individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] When evaluation is made through more strict or accurate diagnostic methods, the prevalence of asymmetry can approach or exceed 50%. [7][8][9][10] In determining facial asymmetry, it is known that deviations in the mandible are the most striking characteristic of the disharmony, particularly the lateral displacement of the chin in relation to the midsagittal plane. 2,7,11 Mandibular asymmetry (MA) is frequently found in subjects affected by trauma, syndromes, or other disorders of the craniofacial area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation